Melioidosis in a Returned Traveller - Zain Chagla; Natasha Aleksova; Jaclyn Quirt; Joel Emery; Christian Kraeker; Shariq Haider (Canadian Journal of Infectious Diseases and Medical Microbiology)
Melioidosis is an infection endemic to Southeast Asia and Northern Australia, and is associated with significant morbidity and mortality. The present report describes a case of chronic melioidosis in a returning traveller from the Philippines. Clinical suspicion of this illness is warranted in individuals with a history of travel to endemic regions. Safety in handling clinical specimens is paramount because laboratory transmission has been described.